The Impact of Maltitol-Sweetened Chewing Gum on the Dental Plaque Biofilm Microbiota Composition - Keijser, Bart J. F.; van den Broek, Tim J.; Slot, Dagmar E.; van Twillert, Lodewic; Kool, Jolanda; Thabuis, Clémentine; Ossendrijver, Michel; van der Weijden, Fridus A.; Montijn, Roy C. (Frontiers in Microbiology, 2018)
Background: The oral cavity harbors a complex microbial ecosystem, intimately related to oral health and disease. The use of polyol sweetened gum is believed to benefit oral health through stimulation of salivary flow and impacting oral pathogenic bacteria. Maltitol is often used as sweetener in food products. This study aimed to establish the in vivo effects of frequent consumption of maltitol sweetened chewing gum on the of dental plaque microbiota in healthy volunteers and to establish the cellular and molecular effects by in vitro cultivation and transcriptional analysis. Results: An intervention study was performed in 153 volunteers, randomly assigned to three groups (www.trialregister.nl; NTR4165). One group was requested to use maltitol gum five times daily, one group used gum-base and the third group did not use chewing gum. At day-0 and day-28 24hr-accumulated supragingival plaque was collected at the lingual sites of the lower jaw and the buccal sites of the upper jaw and analyzed by 16s ribosomal rRNA gene sequencing. At day 42, two weeks after completion of the study, lower jaw samples were collected and analyzed. The upper buccal plaque microbiota composition had lower bacterial levels and higher relative abundances of (facultative) aerobic species compared to the lower lingual sites. There was no difference in bacterial community structure between any of the three study groups (PERMANOVA). Significant lower abundance of several bacterial phylotypes was found in maltitol gum group compared to the gum base group, including Actinomyces massiliensis HOT 852 and Lautropia mirabilis HOT 022. Cultivation studies confirmed growth inhibition of A. massiliensis and A. johnsonii by maltitol at levels of 1% and higher. Transcriptome analysis of A. massiliensis revealed that exposure to maltitol resulted in changes in the expression of genes linked to osmoregulation, biofilm formation and central carbon metabolism. Conclusions: The results showed that chewing itself only marginally impacted the plaque microbiota composition. Use of maltitol sweetened gum lowered abundance of several bacterial species. Importantly, the species impacted play a key role in the early formation of dental biofilms. Further studies are required to establish if frequent use of maltitol gum impacts early dental plaque biofilm